CODE SWITCHING AND THE DEVELOPMENT OF LINGUISTIC SYSTEM OF SIMULTANEOUS BILINGUAL CHILDREN - Leni Amelia Suek (Englisia: Journal of Language, Education, and Humanities, 2017)
Code switching and code mixing are the phenomena commonly seen done by a bilingual. This behavior is influenced by several aspects such as the linguistic system, sociolinguistics, pragmatics, and language competence of the bilingual. If children are able to distinguish two different languages since early age, they will be considered simultaneous bilinguals. They show that they develop multiple, rather than single, linguistic systems. However, it was understood that code switching and code mixing were due to the failure in using proper words, language features, and sociolinguistic competence. Yet, recent studies have shown that bilingual children are able to use both languages proficiently with no signs of confusion or failure in language use. This ability also does not hinder their cognitive development.